Characterization of macroscopic erosion of castellated and flat tungsten surfaces under ITER-like transient plasma loads - Myroshnyk, M.O.; Herashchenko, S.S.; Makhlai, V.A.; Garkusha, I.E.; Aksenov, N.N.; Byrka, O.V.; Chebotarev, V.V.; Kulik, N.V.; Lebedev, S.I.; Shevchuk, P.B.; Staltsov, V.V. (Вопросы атомной науки и техники, 2019)
The damages of tungsten targets with different geometries under repetitive transient hydrogen plasma loads have been studied with a quasi-stationary plasma accelerator QSPA Kh-50. The results of the experiments on target with geometry close to ITER divertor reference design have been compared to results of previous experiments on flat target. The plasma stream parameters were relevant to ITER ELMs (surface heat load above the melting (0.6 MJ/m²) and below the evaporation (1.1 MJ/m²) thresholds of tungsten and pulse duration of 0.25 ms). Surface erosion and dynamics of erosion products have been investigated in the course of repetitive plasma pulses. The crack networks and progressive corrugation occurred on the surface of all the targets exposed to a large number of plasma pulses. Melt motion leads to grow of protuberances on edges of castellated target units. Unlike the flat targets, the separation of liquid/solid particles from the edges of the units is the most significant source of the castellated targets erosion. Вивчено пошкодження вольфрамових мішеней з різною геометрією при повторюваних імпульсних навантаженнях водневої плазмою в квазістаціонарному плазмовому прискорювачі КСПП Х-50. Результати експериментів з мішенню, що має геометрію близьку до конструкції дивертора IТЕР, зіставлені з результатами для пласких мішеней. Параметри потоків плазми обрані близькими до ELM в ІТЕР (поверхневе теплове навантаження вище порога плавлення (0,6 МДж/м²) та нижче порога випаровування вольфраму (1,1 МДж/м²), тривалість імпульсу 0,25 мс). Представлена характеристика ерозії поверхонь і ежекції частинок з мішеней в умовах повторюваних плазмових імпульсів. На поверхнях мішеней, опромінених великою кількістю плазмових імпульсів, виявлені сітки тріщин і виражена хвиляста структура. Рух розплаву призводить до зростання виступів на краях елементів зубчастої мішені. На відміну від плоских мішеней відділення рідких/твердих частинок з країв елементів становить найбільш істотне джерело ерозії зубчастих мішеней. Изучены повреждения вольфрамовых мишеней с различной геометрией при повторяющихся импульсных нагрузках водородной плазмой в квазистационарном плазменном ускорителе КСПУ Х-50. Результаты экспериментов с мишенью, имеющей близкую к конструкции дивертора ИТЭР геометрию, сопоставлены с результатами для плоских мишеней. Параметры потоков плазмы выбраны близкими к ELM в ИТЭР (поверхностная тепловая нагрузка выше порога плавления (0,6 МДж/м²) и ниже порога испарения вольфрама (1,1 МДж/м²), длительность импульса 0,25 мс). Представлена характеристика эрозии поверхностей и эжекции частиц с мишеней в условиях повторяющихся плазменных импульсов. На поверхностях мишеней, облученных большим количеством плазменных импульсов, обнаружены сетки трещин и выраженная волнистая структура. Движение расплава приводит к росту выступов на краях элементов зубчатой мишени. В отличиe от плоских мишеней отделение жидких/твердых частиц с краев элементов составляет наиболее существенный источник эрозии зубчатых мишеней.